2020
DOI: 10.1097/scs.0000000000007182
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Clinical Use of Concentrated Growth Factor in Maxillofacial Regenerative Medicine

Abstract: Different strategies have been utilized to facilitate mineralized/soft tissues. Concentrated growth factor (CGF) emerges as a promising biomaterial for regenerative therapy due to high levels of platelets, growth factors, and nucleated cells entrapped in the fibrin scaffold. This review aimed to collect extensive studies on CGF used in maxillofacial regenerative medicine, discussing current obstacles, and expressing some considerations of CGF use. Articles were retrieved systematically without time limitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Many methods have been used to help bone regeneration in clinical therapy, including bone graft, 6 growth factors materials 10 and photodynamics therapy 14 . Researchers have begun to use low‐level lasers to treat disorders since 1980 because these lasers do not produce heat during their work 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been used to help bone regeneration in clinical therapy, including bone graft, 6 growth factors materials 10 and photodynamics therapy 14 . Researchers have begun to use low‐level lasers to treat disorders since 1980 because these lasers do not produce heat during their work 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Deep periodontal pockets and bone defects formed in the distal side of the second molar after the operation were currently treated by the placement of autogenous or xenogeneic bone grafts, 6 artificial bone material, guided tissue regeneration 7,8 or tissue engineering 9 . All of these methods have shown significant curative effects; however, their drawbacks of being expensive or technically sensitive limited their uses 10 . Recently, it has been found that concentrated growth factor (CGF)‐like growth factor gel, which is extracted from venous blood by centrifugation, and rich in a variety of biological factors important for growth and development, as it can accelerate the formation of healed new bone, promotes the repair of bone defects by providing scaffolds and high concentrations of growth factors 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that CGF could not only accelerate soft-tissue healing and early bone formation but also reduce post-surgical edema, pain, trismus, and discomfort. [ 36 , 37 ] Other literatures have shown that new bone formation was significantly increased in the defective bone region filled with CGF and Bio-Oss compared to Bio-Oss only. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2021) (21) elaborated on the role and potential application of CGF in the regeneration of the dentin-pulp complex, many in vitro studies have shown that CGF can promote the proliferation and migration of dental stem cells. Chen et al (2021) (22) stated that CGF has been most evaluated in implant-related therapies and maxillofacial bone regeneration, and most of these articles showed good results. CGF is the latest generation of concentrated platelets, and Chen and Jiang (2020) (23) elaborated that CGF has a good application in facial rejuvenation, cartilage transplantation, facial bone defects, facial peripheral nerve injury and trauma.…”
Section: Discussionmentioning
confidence: 99%